Review Language Contact and Language Change in Ethiopia von Yvonne Treis - Treis, Yvonne (AAeO - Afrikanistik-Aegyptologie-Online, 2011)
The present book is one of the many outcomes of research carried out at the University of Mainz on language contact phenomena in the Ethiopian Linguistic Area. While a previous book edited by Joachim Crass and Ronny Meyer concentrated on copulas, focus morphemes and deictic elements (Crass & Meyer 2007), the present work does not have a particular thematic focus; rather it deals with various contact-induced and internally motivated language change phenomena in Omotic, Cushitic and Ethiosemitic languages. Apart from the introduction by the editors, the book contains six articles. In the following sections, the articles will be summarised and assessed individually. The review will end with a general evaluation of the book.